Bile acids induce IL-1α and drive NLRP3 inflammasome-independent production of IL-1β in murine dendritic cells - Oleszycka, Ewa; O’Brien, Eoin C.; Freeley, Michael; Lavelle, Ed C.; Long, Aideen (Frontiers in Immunology, 2023)
Bile acids are amphipathic molecules that are synthesized from cholesterol in the liver and facilitate intestinal absorption of lipids and nutrients. They are released into the small intestine upon ingestion of a meal where intestinal bacteria can modify primary into secondary bile acids. Bile acids are cytotoxic at high concentrations and have been associated with inflammatory diseases such as liver inflammation and Barrett's Oesophagus. Although bile acids induce pro-inflammatory signalling, their role in inducing innate immune cytokines and inflammation has not been fully explored to date.Here we demonstrate that the bile acids, deoxycholic acid (DCA) and chenodeoxycholic acid (CDCA) induce IL-1α and IL-1β secretion in vitro in primed bone marrow derived dendritic cells (BMDCs). The secretion of IL-1β was found not to require expression of NLRP3, ASC or caspase-1 activity; we can't rule out all inflammasomes. Furthermore, DCA and CDCA were shown to induce the recruitment of neutrophils and monocytes to the site of injection an intraperitoneal model of inflammation. This study further underlines a mechanistic role for bile acids in the pathogenesis of inflammatory diseases through stimulating the production of pro-inflammatory cytokines and recruitment of innate immune cells.